Reframing Religious Experience through ‘Ālam al-Mithāl: A Philosophical and Mystical Perspective in Islamic Thought - Al Walid, Kholid; Toresano, Waode Zainab Zilullah; Widjayanti, Rosmaria Syafariyah; Norman, Nurul Ain (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This paper investigates the philosophical and mystical concept of ‘Ālam al-Mithāl (The Imaginal World) in Islamic thought as analternative framework for understanding religious experience. Despite the acknowledgement of its importance, contemporary discourse has yet to undertake a systematic philosophical inquiry into how ‘Ālam al-Mithāl, as a spiritual epistemology, provides rational grounds for affirming the objective reality and transformative capacity of religious experiences, surpassing interpretations that reduce such experiences to merely subjective or psychological interpretations. This research addresses this gap by analyzing how Mullā Ṣadrā’s ontological principle of Aṣālat al-wujūd (fundamentality of existence) and epistemological principle of Ittiḥād al-‘Āqil wa al-Ma‘qūl (union of the intellect and the intelligible) substantiate the objective reality of experiences within ‘Ālam al-Mithāl. The study further examines the essential role of ta’wīl (esoteric interpretation) in unveiling the deeper meanings of symbolic encounters in this realm. By integrating these philosophical principles, the paper demonstrates how ‘Ālam al-Mithāl offers a rigorous framework for validating religious experiences as genuine perceptual events within an objective, intermediate reality. This framework challenges reductionist modern paradigms and highlights the imaginal realm’s significance in self-realization and the acquisition of divine knowledge.